HUBUNGAN ANTARA PERSEPSI TENTANG GAYA KEPEMIMPINAN DIREKTUR DENGAN PRODUKTIVITAS KERJA DOSEN POLITEKNIK ILMU PELAYARAN (PIP) MAKASSAR - Jean Novita Christanty Budiman (Widyariset, 2009)
This research was aimed: (1) to describe the perception of lecturers on director's leadership style,  (2) to describe lecturers' working productivity, and (3) to know the correlation between the perception on director's leadership style and lecturers' working productivity at PIP Makassar. This research population was based on all lecturers (97) at PIP Makassar. However; the samples were randomly taken 55% from the population. The data were collected by questionnaire and interview methods, then they were analyzed by using descriptive statistics to describe the perception of lecturers on director's leadership style and lecturers 'working productivity. The correlation between the perception of lecturers on director 's leadership style and lecturers' working productivity was analyzed by a simple correlation. The results of this research showed that the perception of lecturers on director's leadership style was in a high category as well as lecturers' working productivity. By correlation analysis, it was found that there was a positive and a significant correlation (0.563) between the perception on director 's leadership style and lecturers' working productivity at PIP Makassar.